Usaha Meningkatkan Kuantitas Dan Kualitas Hasil Kacang Hijau(Vigna radinata(L) Willczek) dengan inokulasi rhizobium dan pupuk TSP - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The experiment was aimed to study and effort to improve quantity and quality of mungbean seed by Rhizobium inoculation and phosphate fertilizer. The research was conducted at Laboratory of Seed Technology, Faculty of Agriculture, Gadjah Mada University and Nogotirto field, Sleman from September to December 1994. A factorial experiment was used and arranged in Randomized Complete Block Design with three replications for quantity of seed test in the field and Completly Randomized Design with four replications for quality of seed test in the laboratory. The experiment applied Rhizobium inoculation and no Rhizobium combined with four levels of TSP at 0, 45, 90 and 135 kg/ha. The result of this experiment indicated that the application of Rhizobium could improve the quantity and quality of mungbean seed. Phosphate fertilizer increased the quantity and quality of mungbean seed yield by the application of TSP at 45 kg and 90 kg/ha.